PENDAMPINGAN PERSIAPAN PENDIRIAN BADAN USAHA MILIK KAMPUNG SERMAYAM INDAH - Muhammad Awal; Anthonia Karolina Rejo Lobwaer; Syahruddin Syahruddin (Musamus Devotion Journal, 2020)
Referring to the situation of the limited understanding of the officials and the people of the village of Sermayam Indah, Tanah Miring District, this assistance aims to improve the understanding of officials and documents on the preparation of BUMKam establishment. Using savings methods, interviews, lectures and discussions, the stages of Identification and Preparation for Implementation, Socialization, Preparation for Establishment consisting of Discussion of Draft Draft by the Formulating Team, Drafting Approval Meeting by the Village Deliberation Board (BAMUSKAM), Submission of Outcome Documents for Establishing BUMKam. The implementation of the activity was initiated with a socialization program to improve the understanding of the village apparatus regarding the Village Enterprises, with the presentation of the procedures for establishing BUMKam and the Economic Potential and the Formulation of the Formulation Team, followed up by the assistance of the drafting team and the Village Consultative Body. This assistance resulted in the Design of AD and ART Periods, Organizational Structure, Business Logos, Business Names and Types of Businesses. So it was concluded that the Village Owned Enterprises (BUMKam) had not yet formed due to limited understanding and initial documents of the establishment could be overcome by the village through collaboration with universities and districts. Assistance can run optimally if the College Assistance Team communicates intensely with the District Officials and Village Officials